2016
DOI: 10.3402/meo.v21.29874
|View full text |Cite
|
Sign up to set email alerts
|

What does the multiple mini interview have to offer over the panel interview?

Abstract: IntroductionThis paper compares the panel interview (PI) performance with the multiple mini interview (MMI) performance and indication of behavioural concerns of a sample of medical school applicants. The acceptability of the MMI was also assessed.Materials and methodsAll applicants shortlisted for a PI were invited to an MMI. Applicants attended a 30-min PI with two faculty interviewers followed by an MMI consisting of ten 8-min stations. Applicants were assessed on their performance at each MMI station by on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 23 publications
2
33
0
Order By: Relevance
“…Psychology students admitted through an admission procedure including a cognitive admission tests and Multiple Mini Interviews have been shown to outperform psychology students admitted based on their SSGPA (Makransky et al, 2016). Although it is also consistent with most other available information, most studies investigating predictors of academic success other than SSGPA focus on medical programs, and those are currently undecided on the "best practices" in the implementation of admission tools other than SSGPA (Richardson et al, 2012;Schripsema et al, 2014Schripsema et al, , 2017Shulruf and Shaw, 2015;Patterson et al, 2016;Pau et al, 2016;Sladek et al, 2016;Wouters et al, 2017). Note that NCS is quite susceptible to social desirability and that the literature does not allow firm conclusions on the validity of these and other non-cognitive factors (Patterson et al, 2016).…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Psychology students admitted through an admission procedure including a cognitive admission tests and Multiple Mini Interviews have been shown to outperform psychology students admitted based on their SSGPA (Makransky et al, 2016). Although it is also consistent with most other available information, most studies investigating predictors of academic success other than SSGPA focus on medical programs, and those are currently undecided on the "best practices" in the implementation of admission tools other than SSGPA (Richardson et al, 2012;Schripsema et al, 2014Schripsema et al, , 2017Shulruf and Shaw, 2015;Patterson et al, 2016;Pau et al, 2016;Sladek et al, 2016;Wouters et al, 2017). Note that NCS is quite susceptible to social desirability and that the literature does not allow firm conclusions on the validity of these and other non-cognitive factors (Patterson et al, 2016).…”
Section: Discussionsupporting
confidence: 57%
“…If the selection outcomes apparently do not sufficiently match the goals of the admission committee as students progress (or not) through their first, second and third year, the admission procedure will be adjusted. We argue that individual differences in which tool accurately predicts future academic success might be worth further investigation in the light of actual and desired levels of diversity in student populations (Stegers-Jager et al, 2015;Pau et al, 2016) in relation to both open admission and selection. It depends on the goals of the admission committee whether preventing rejection of applicants that would be successful students (preventing misses) is considered more important than preventing admission of students that will fail (preventing false alarms).…”
Section: Suggestionsmentioning
confidence: 98%
See 1 more Smart Citation
“…As expected, the MMI shows little correlation with indices of cognitive function such as grade point averages. 10 Although good content validity implies sampling across the entire breadth of attributes required for competent general practice, the MMI focuses on a subset of attributes that are not primarily cognitive. Further complicating the concept of content validity is that issues such as the context of general practice require some knowledge upon which to apply values and attitudes.…”
Section: Introductionmentioning
confidence: 99%
“…Several research studies have shown MMIs are more valid and reliable than traditional interviews [2,[4][5][6][7][8][9][10][11][12][13][14][15][16][17]. When assessing non-cognitive attributes, a candidate's qualities in one domain cannot be generalized into another due to their context specificities, and thus, it is not feasible to predict a candidate's performance in one domain based on his/her performance in other domains [18].…”
Section: Introductionmentioning
confidence: 99%